Value relevance of proportionate consolidation versus the equity method: Evidence from Hong Kong - Stella So; Kar Shun Wong; Feida Zhang; Xu Zhang (China Journal of Accounting Research, 2018)
Whether proportionate consolidation (PC) or the equity method (EM) provides more informative financial statements is a controversial issue. This study uses data from listed companies in Hong Kong to investigate the value relevance of the EM compared with PC during 2005-2008 when the local word-for-word equivalent HKAS 31 offered the same options. The results of this study provide evidence that PC does not offer higher value relevance than the EM. PC's horizontal aggregation of a portion of the operations, assets and liabilities of the jointly controlled entities with those of the venturer is less informative to investors than the EM's vertical aggregation.
Keywords: 650; Value relevance; Proportional consolidation method; Equity method; Financial statements